EKSPLORASI KERAGAMAN GENETIK TANAMAN JAHE LOKAL SULAWESI TENGGARA DAN UPAYA PEMANFAATANNYA DALAM PROGRAM PEMULIAAN - Boer, Dirvamena; Karimuna, La (Jurnal Agroteknos, 2013)
Ginger (Zingiber officinale Rosc.) is one of the spices and medicinal plants which has many benefits and usefulness. Currently ginger production in Indonesia is still very low, du e to limited sources of genes possessed by plant breeders (narrow genetic stock), therefore it is necessary to obtain new genetic diversity. The purpose of this study was to conduct exploration activities to collect local ginger germplasm in Southeast Sulawesi to get information in the form of (a) genetic diversity of accessions, (b) determination that can be used to identify germplasm genetic diversity of ginger of Southeast Sulawesi, (c) description of the collected ginger types, for the benefit of ginger crop improvement through breeding programs. This study began with exploration activities, then planting accessions for collection and conservation which will be utilized in various ginger breeding programs. The results of exploration obtained as many as 18 accessions from Kendari, Konawe, Bombana, Muna and Buton regencies. Results of the collection of some areas of Southeast Sulawesi showed that ginger genetic diversity was quite high, seen from the morphological appearances of the rhizome. Based on the size, shape and color of the rhizome, the ginger accessions of Southeast Sulawesi can be classified into three major groups, i.e. large white/yellow ginger, small white/yellow ginger, and red ginger. White ginger was large and more attractive than red ginger, but less spicy aroma due to its low essential oil content, and less disease resistant, but high productivity. Keywords: ginger, Zingiber officinale, genetic diversity